2017
DOI: 10.3233/jad-160675
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Association between Donepezil and Choline Alphoscerate on Behavioral Disturbances in Alzheimer’s Disease: Interim Results of the ASCOMALVA Trial

Abstract: Patients treated with donepezil plus choline alphoscerate showed a lower level of behavioral disturbances than subjects treated with donepezil only, suggesting that the association can have beneficial effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 62 publications
1
17
0
1
Order By: Relevance
“…Causes and pathophysiology of BPSD are incompletely understood. 37 Likewise, pathophysiology, phenomenology, main clinical correlates, and long-term evolution of disinhibition symptom in dementia remain unclear. 38 Accordingly, it might be difficult to elucidate the association between memantine and improvement of disinhibition symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Causes and pathophysiology of BPSD are incompletely understood. 37 Likewise, pathophysiology, phenomenology, main clinical correlates, and long-term evolution of disinhibition symptom in dementia remain unclear. 38 Accordingly, it might be difficult to elucidate the association between memantine and improvement of disinhibition symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In the ASCOMALVA study, comparing a subgroup of AD individuals (n = 56) receiving a combination of donepezil and choline alphoscerate (a cholinergic precursor) versus a subgroup (n = 57) with donepezil alone (24-month treatment period), the combined treatment was more effective on apathy levels than donepezil alone (Rea et al, 2015;Carotenuto et al, 2017).…”
Section: Randomized Controlled Trials (Rct)mentioning
confidence: 99%
“…Choline alfoscerate (alpha GPC) at a dose of 400mg TID has been found to improve cognition and global function in patients with mild to moderate AD when used over a period of 6 months [111]. This supplement, when taken with donepezil, also decreased mood symptoms in this patient population [112]. A 2010 meta-analysis found that another form of choline (CDP choline) has positive effects on several cognitive domains [113].…”
Section: Cholinementioning
confidence: 99%